Economic viability of a large vessel mesopelagic fishery under ecological uncertainty - Vastenhoud, Berthe M. J.; Bastardie, Francois; Andersen, Ken H.; Speirs, Douglas C.; Nielsen, J. Rasmus (Frontiers in Marine Science, 2023)
Motivated by the global rise in demand for marine products, there is increased interest in exploitation of the mesopelagic zone. However, the feasibility of this potential fishery remains uncertain, partly due to limited biological data and knowledge on sustainability of exploitation, and due to questions related to its economic viability. Consequently, there is a demand for better insights into these factors before any commencement of a fishery. Here we use the DISPLACE individual-vessel based bio-economic model to evaluate economic and biological trade-offs of a fishery on Maurolicus muelleri and Benthosema glaciale, the main potential target fish species in the mesopelagic zone of the Northeast Atlantic. We found that a fish price between 1.6-5.0 €/kg is necessary for mesopelagic resources to assure a profitable mesopelagic fishery, which is twice that expected for species with similar fat content. These high fish prices are necessary to cover the high fuel consumption costs due to the distant fishing grounds. Furthermore, the distance of the fishing grounds makes the fuel tank capacity a limiting factor for the fishery. A first evaluation of preliminary harvest control strategies indicated that a low fishing mortality of F = 0.2 year-1 resulted in the highest potential profitability of the fishery. Restriction of gear mesh sizes did not significantly affect the profitability of the fishery. We show that the current ecological uncertainties, especially regarding the life-history, species-specific and spatio-temporal abundance and distribution estimates have a significant impact on the estimates of potential viability of the fishery. It is therefore of the utmost importance to gain more insights in those factors before investments are made into the development of such fishery.